Street Art and the Struggle for Public Space - Muttaqin, M. Zaenul (SAUC - Street Art and Urban Creativity (repository), 2023)
The film entitled "Coretan Seni Dibalik Vandalisme" is an Indonesian-language documentary film that offers street art from a broader perspective, beyond the values ??of legality and democracy. The views of artists, observers, and academics are important to capture the reorientation of street art which has been commonly called vandalism.